The Contentious Implementation of Social Programs: The Registration of the «Vaso De Leche» Program in Villa El Salvador, Lima, Peru (2002-2010) - García, Luis (2014)
This study analyzes factors that allow local officials to overcome design distortions generated during the process of registering beneficiaries of the «Vaso de Leche» Program in a context in which these beneficiaries are powerful social actors who have a capacity for collective action. This study was conducted between 2002 and 2010 in Villa El Salvador, a district of metropolitan Lima. Villa El Salvador municipal authorities selected beneficiaries without considering the target population as established by the official regulations. This variation from established norms is understood in this study as a «design distortion». Starting in 2004, this distortion was reduced with the introduction of a registry for the program that did follow official norms. In the literature, control mechanisms are highlighted as a key strategy for correcting design distortions. This study suggests an alternative focus: change also depends on the decisions of local officials to establish alliances with program target groups and concludes that such decisions are fundamental to understand the program implementation in contentious settings.